the Persepsi Remaja Terhadap Bermain Game Online Atlantica dalam Penguasaan Kosa Kata Bahasa Inggris - Butar-Butar, Jhuan Carlos; Ilmi, Djauzi (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2024)
This Thesis entitled “The Teenagers’ Perception on The Playing of Atlantica Online Game in English Vocabulary Mastery” This is a research of the influence of online gaming in the development of English vocabulary mastery teenagers. The purpose of research is that today’s teenagers play games not just for fun, we can learn English while playing games. This research uses qualitative methods. This research uses behaviorism theory. This research is conducted in Medan and several gamers became participant. Data of the research are the words contained in Atlantica Online, books, journal, and article who made inquiries to find meaning in Indonesian. The data source of this thesis is online game ‘Atlantica Online’. To make easy the finding of research results, the researcher use tables and diagrams. The results showed that, how frequently teenagers influential within understanding the vocabulary mastery contained in Atlantica Online.